National study of child sexual abuse cases in Oman: Characteristics and medical-legal outcomes - Muna Alshekaili; Mohammed Ali Al-Marzoqi; Salim Al-Huseini; M Mazharul Islam; Fatima Al-Sulaimani; Walid Hassan; Yahya Alkalbani; Mohamed Al Breiki; Abdullah Al-Madhani; Nithila Mariam Roy; Ibrahim Al-Zakwani; Aishwarya Ganesh; et al. (Heliyon)
Background: To stay abreast of the best international practices, the Arab Gulf countries have ratified the United Nations Convention on the Rights of the Child Treaty, which includes clauses on safeguarding the well-being of children against child abuse and neglect. The enactment of laws, policies, and facilities designed to protect the rights of the child has not yet been studied to determine whether it leads to appropriate legal dispositions against perpetrators of child sexual abuse (CSA) in Oman. Aims: This study has been launched to address two interrelated objectives; (i) describe the characteristics of CSA victims and perpetrators and (ii) examine factors associated with medicolegal findings and judicial results for CSA complainants in Oman. Methods: Data come from a retrospective survey that covered one year from January 2017 to December 2017. Data from participants who met the study criteria were drawn from statistics published by the Oman Public Prosecution. The study was designed to obtain sociodemographic characteristics of victims and perpetrators of CSA, the types of prevalent cases of CSA, whether CSA was the result of family or extrafamilial encounters, and the characteristics of medical findings and legal results. Result: During the designated period, 269 victims and 269 defendants were identified. Most of the victims were boys (55.8 %), and their ages ranged from 9 to 15 years (mean age 12 years). Among the perpetrators, all were men, with ages ranging between 20 and 40 years (mean age 28.3 years). The vast majority (96.7 %) of reported cases were of extrafamilial type. The identified types of CSA constituted inappropriate sexual behavior towards children (63 %), followed by sodomization (26 %) and vaginal coitus (7.1 %). The factors that explained the results in favour of the victims in the medicolegal findings included the female sex of the victim (AOR = 2.78, 95%CI = 1.01–7.87), and the ages of the victim between 8 and 12 years (AOR = 4.29, 95 % CI = 1.51–12.16). Among the cases that were tried in court, 76 % were convicted and sentenced to an average of 30 months in correctional facilities. Factors associated with the conviction of the perpetrator were victims' ages between 13 and 17 years (AOR = 3.45, 95 % CI = 1.22 to 9.79), the type of abuse was sodomization (AOR = 1.95, 95%CI = 1.08–6.78), and cases that included positive forensic results (AOR = 2.66, 95 % CI = 1.23 to 8.45). Discussion: To date, studies on medical-legal and judicial outcomes of CSA in developing countries have received little attention. The present sentinel study lays the foundation for future studies using the robust methodology required to further scrutinize the medicolegal findings and judicial results of CSA in similar regions of the Middle East. The present findings also suggest that the CSA trends in Oman tend to echo those reported from developed countries, but there are also culture-specific factors that shape reporting, as well as medico-legal and judicial outcomes.